Becoming Bikini Bodybuilders: Challenges and Rewards of Ordinary Women Stepping on Stage - Michalikova, Nina (Lexington Books, 2023)
Becoming Bikini Bodybuilders: Challenges and Rewards of Ordinary Women Stepping on Stage offers an insight into the bikini category of natural female bodybuilding by revealing benefits and challenges experienced by ordinary women who decide to become bikini bodybuilders. Nina Michalikova challenges prevailing misconceptions and shows that not all female athletes follow extreme training and dietary measures for prolonged periods of time to achieve their desired physique. By highlighting the positive aspects of bikini bodybuilding, this book breaks the stereotypes of a “typical bikini competitor” as a hyper-sexualized woman with underlying health issues. In addition to studying a little understood population of bikini athletes, the study uses an innovative methodology to examine the topic.